Photolabile RuII Half‐Sandwich Complexes Suitable for Developing "Caged" Compounds: Chemical Investigation and Unexpected Dinuclear Species with Bridging Diamine Ligands. Issue 27 (2nd August 2013) - Finazzi, Ilaria; Bratsos, Ioannis; Gianferrara, Teresa; Bergamo, Alberta; Demitri, Nicola; Balducci, Gabriele; Alessio, Enzo
Abstract: Six half‐sandwich Ru II coordination compounds of the general formula [Ru([9]aneS3 )(L–L)(L′)][PF6 ] n {2 –7 ; [9]aneS3 = 1, 4, 7‐trithiacyclononane, L–L = 2, 2′‐bipyridine (bpy), 1, 2‐diaminoethane (en), (±)‐ trans ‐1, 2‐diaminocyclohexane (dach), picolinate (pic); L′ = pyridine (py), 3‐acetylpyridine (3‐acpy), imidazole (im); n = 1 or 2, depending on the nature of L–L} were prepared and characterized. If irradiated with blue light ( λ = 400–490 nm) in aqueous solution, they readily dissociate the monodentate L′ ligand to generate selectively the corresponding aqua species. The extent and rate of photoinduced ligand release depend primarily on the nature of the chelating ligand (bpy >> en ≈ dach > pic) and, to a minor extent, on that of the leaving ligand (py > im > 3‐acpy). Photolabile compounds2 –5 showed no significant antiproliferative activity against the MDA‐MB‐231 human mammary carcinoma cell line, both in the dark and upon irradiation with blue light. The clean photodissociation process that characterizes this class of half‐sandwich Ru II compounds, and the substantial lack of toxicity of the photogenerated Ru aqua species, suggest that they might be suitable for the preparation of "caged" Ru II compounds. In the frame of this work, two unexpected dinuclear compounds, namely, [{Ru([9]aneS3 )(en)}2 (μ‐en)][CF3 SO3 ]4 (9 ) and [{Ru([9]aneS3 )}2 (μ‐dach)(μ‐CH3 O)2 ][CF3 SO3 ]2 · 2CH3 OH (10 )―both containing rare examples of bridging en and dach ligands―were also isolated and structurally characterized. Abstract : If irradiated with visible light in aqueous solution, the photolabile Ru II half‐sandwich coordination compounds [Ru([9]aneS3 )(L–L)(L′)] 2+ ([9]aneS3 = 1, 4, 7‐trithiacyclononane; L–L = 1, 2‐diaminoethane, etc.; L′ = pyridine, etc.) readily dissociate L′ to generate the corresponding aqua species.